Psychoeducation to Improve Work Safety Culture at ABC Hospital: Emloyee Awareness - Firmadani, Renata Dian; Djudiyah, Djudiyah (Tinta Emas Institute, 2025)
Hospital Occupational Safety and Health Culture (K3RS) is an important aspect in ensuring the safety of healthcare workers, patients, and the hospital environment. However, in practice, low levels of employee awareness regarding the reporting of occupational accident incidents are still found, particularly for accidents that are considered minor. This study aimed to evaluate the effectiveness of a psychoeducational program in improving employee awareness of K3RS among nurses and midwives at ABC Hospital. This study employed a one-group pretest and posttest experimental design with a total of 10 healthcare workers consisting of nurses and midwives. The intervention included K3RS psychoeducation, reinforcement of work safety attitudes and values, and simulation of occupational accident incident reporting. Data were collected using a questionnaire administered via Google Forms. The results indicated an increase in employee awareness after the psychoeducational intervention, as reflected by improved participants' understanding of the types and categories of occupational accidents and increased awareness of the importance of incident reporting.